AFFECT AS APPRAISAL SYSTEM ON SOCIAL MEDIA “INSTAGRAM” - Zohri Hamdani (Journal of English Education and Linguistics, 2021)
This study aimed to identify and describe the forms of Attitude as one of the aspects of Appraisal theory.. The object of this research is @officialtbistainmadina instragram account, especially on the last 15 comments out of a total of 47 comments published on November 4, 2020. Collecting data in this study is observation. This observation method is also called the observing method because the data is obtained by listening to the use of language. The data analysis technique in this study uses the referential equivalent method. The result of study shown that the various forms of Attitude that appear in these comments tend to use one of the three aspects in the form of Attitude, namely the aspect Affect with words such as "like", "delicious", "tempting".